(untitled) (Semiárida, 2021)
Grasslands in arid and semiarid regions suffer ecological degradation and production limitations. A management alternative to reverse this situation is the sowing of megathermal forage species. The objective was to evaluate vegetative and reproductive characters for the establishment of native and introduced forage grasses of the semiarid pampean region. The species evaluated were: the native Leptochloa crinita and Pappophorum caespitosum and the introduced ones Eragrostis curvula, Eragrostis superba, Tetrachne dregei, Digitaria eriantha and Panicum coloratum. Survival (Ix), Canopy height (AM), Canopy diameter (DM), Number of tillers (NM), Length of floral stems (LVF), Number of floral stems (NVF), Number of seeds per plant (NSP) and Weight of thousand seeds (PMS) were determined. Survival, 3 months after implantation, was high and without significant differences between species. P. coloratum obtained the highest values regarding: NVF (3 and 12 months), LVF (12 months), DM (10 and 12 months) and PMS (4 and 14 months after its implantation). D. eriantha obtained the highest values in: LVF (3 months) and AM (3 and 12 months); while E. curvula in NM (10 and 12 months), T. dregei in NSP (14 months) and P. caespitosum in NSP (4 months after implantation) and had significant differences with the rest of the species. It is feasible to implant the evaluated species, because they show high survival, good propagation by tillering (introduced) and high seed production (native).